Korelasi Antara Aktivitas Antioksidan dengan Kandungan Senyawa Fenolik dan Lokasi Tumbuh Tanaman Celosia argentea Linn. - Wardani, Yulia Kusma; Elok Kristiani, Elizabeth Betty; Sucahyo, S (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Celosia argentea Linn. is a herbaceous plant of Amaranthaceae family. The plant has antioxidant property. The antioxidant capacity is determined by the existence of secondary metabolite of which phenolics compound is one of them. This research aim was to determine the correlation between phenolics compound content and the growing environment with the antioxidant activity of Celosia argentea Linn. The plants were obtained from three different locations in Salatiga area included Ngronggo Village Landfill (TPA), Jalan Raya Lingkar Selatan (JLS), and in Blotongan Housing Complex areas (PB). The fresh leaves of the plant were extracted by maceration method using ethanol 96% in the room temperature for 48 hours. The determination the phenolics content was using Folin-Ciocalteu method, while antioxidant activity using DPPH assay. The phenolis content of C. argentea Linn. leaves were 10,22; 6,99; 4,97 ppm from TPA, JLS, and PB respectively, while the IC50 values of antioxidant activity were 2,98; 3,18; and 3,35 ppm respectively. There were a correlation between antioxidant activity and phenolics compound with the growing environment of C. argentea Linn. The higher of phenolics compound content, the lower the IC50 value (higher an antioxidant activity). The phenolics content was also has a strong correlation with environment. Â